Successful Management of Culture-Negative Fungal Keratitis with Epithelial Keratectomy and Intracameral Fluconazole Injection: A Case Report - Kristian Dernitra; I Gusti Ayu Made Juliari; Ida Ayu Ary Pramita (HM Publisher, 2026)
Background: Fungal keratitis is a major cause of corneal blindness in tropical regions. Microbiological culture often yields negative results in up to 40% of clinically suspected cases, creating diagnostic and therapeutic challenges. This report describes successful management of culture-negative suspected fungal keratitis using epithelial keratectomy combined with intracameral fluconazole injection. Case presentation: A 58-year-old male presented with progressive visual loss in the left eye following mud exposure and irrigation with river water. Examination revealed a 3×3 mm paracentral corneal ulcer with stromal infiltration exceeding one-third depth, satellite lesions, and 1.5 mm hypopyon. Gram stain, potassium hydroxide preparation, and culture were all negative. Based on clinical suspicion of fungal etiology, the patient underwent epithelial keratectomy with intracameral fluconazole injection, supplemented by intensive topical and systemic antifungal therapy. Progressive improvement was observed, with complete hypopyon resolution by day 26 and visual acuity improving from 1/300 to 6/30 over four months. Conclusion: This case demonstrates that timely invasive antifungal intervention guided by clinical judgment can achieve favorable outcomes in culture-negative suspected fungal keratitis. The preservation of useful vision without corneal transplantation is particularly significant in resource-limited settings, underscoring the critical role of clinical decision-making when laboratory confirmation is unavailable.